Utilizing Rice Husk Briquettes in Firing Crucible Furnace for Low Temperature Melting Metals in Nigeria - Musa, N. A.; Akinbode, F. O. (Engineering, Technology & Applied Science Research, 2012)
The search for alternative fuels for firing crucible furnace for low temperature melting metals has become mandatory, as a result of the pollution problem associated with the use of fossil fuels, the expense of electricity and also deforestation as a result of the use of charcoal. An agricultural waste, rice husk, in briquette form was used as an alternative fuel to fire crucible furnace to melt lead, zinc and aluminium. Results showed that lead and zinc melted and reached their pouring temperatures of 3840C and 5300C in 70 minutes and 75 minutes respectively. Aluminium was raised to a maximum temperature of 5200C in 75 and 100 minutes.The average concentration of the pollutants (CO, SO2and NOX) were found to be below the tolerance limit and that of TSP (Total Suspended Particulates) was found to be within the tolerance limit stipulated by Federal Environmental Protection Agency (FEPA) in Nigeria.